beta-Arrestin biased dopamine D2 receptor partial agonists: Synthesis and pharmacological evaluation - Männel, Barbara; Hübner, Harald; Möller, Dorothee; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2017)
beta-Arrestin biased G protein-coupled receptor ligands represent important molecular probes and may increase favorable drug action and safety as novel therapeutics. Starting from recently discovered hydroxy-substituted heterocyclic piperazine scaffolds, we have developed a series of dopamine D-2 receptor ligands with a pyrazolo[1,5-a]pyridine as secondary pharmacophore that is functionalized in position 3 by a formyl or hydroxyiminomethyl substituent. The ligands, especially the benzoxazinone 9d, were found to stimulate substantial beta-arrestin-2 recruitment, while being nearly devoid of activity in a GTP gamma S binding assay. Investigating a new series of truncated analogs lacking a secondary pharmacophore, considerable b-arrestin-2 recruitment in the absence of G protein activation was found, when a 5-hydroxy-2H-benzo[b][1,4]oxazin-3(4H)-one was combined with an N-propyl-substituted 1,4-diazepane (15c). Although 15c displayed reduced potency compared to 9d, the dose-response curves indicate that a hydroxy-substituted heterocyclic primary pharmacophore is sufficient for the functionally selective activation of D2R. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: GPCR; Dopamine receptor; Ligand bias; Functional selectivity; beta-Arrestin; G protein